Enhancement of the production yield of fluorescent silicon nanostructures using silicon-based salts - Laila H. Abuhassan (Universiti Kebangsaan Malaysia, 2010)
The increase in the amount of extracted silicon nanostructures resulting from the incorporation of sodium metasilicon salt in the etching solution was investigated. Silicon nanostructures were prepared in the form of thin fluorescent films via anodisation etching of silicon wafers in aqueous HF/H2O2 solution in the presence of the silicon-based salt. The quality of the fluorescent films was assessed using several nondestructive analytical techniques. The nanostructures produced were then extracted. The harvested nanostuctures were examined for quantitative elemental analysis using atomic absorption spectrophotometry. This investigation was limited to silicon nanostructures with size ≤ 200 nm. The results indicate that the incorporation of the silicate increased the yield of silicon nanostructures production significantly.